Hubungan Faktor Lingkungan Dan Perilaku Masyarakat Dengan Kejadian Demam Berdarah Dengue (DBD) Di Kabupaten Lampung Tengah Tahun 2025 (STIKES Columbia Asia Medan, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. According to the WHO, 40% of the world's population is at risk of dengue fever, with a significant increase in cases in the last two decades, especially in 2019. After declining during the Covid-19 pandemic, cases surged again in 2023, including in previously unaffected areas. In Indonesia, Ministry of Health data shows an increasing trend in cases, with 186,324 cases and 1,120 deaths by week 35 of 2024. Environmental factors and community behavior influence the spread of dengue-causing mosquitoes. This study aims to determine the relationship between these factors and the incidence of dengue fever in Central Lampung Regency. This study aims to determine the relationship between environmental factors and community behavior with the incidence of Dengue Hemorrhagic Fever (DHF) in Central Lampung Regency. This study is an observational analytical study using a case control study design. The research instruments used were questionnaires and observation sheets. The data analysis technique used the chi square test. From the results of the study it is known that out of 9 variables, 4 variables have a relationship with the incidence of DHF, namely the availability of container covers (p value = 0.023 <0.05), frequency of container drainage (p value = 0.001 <0.05), the presence of larvae in containers (p value = 0.006 <0.05), and respondent attitudes (p value = 0.023 <0.05). Based on research in Central Lampung Regency, of the nine variables examined, four were shown to be associated with the incidence of Dengue Hemorrhagic Fever (DHF). Therefore, it is crucial to raise public awareness and routinely implement Dengue Prevention (PSN) or 3M, both independently and collectively. Dengue prevention needs to be carried out not only through sanctions (punishment), but also through a promotive and preventive approach involving individuals, communities, environmental policies, and supervision from relevant agencies. These efforts must be comprehensive and sustainable, involving all levels of society.